Genetic liability to multiple factors and uterine leiomyoma risk: a Mendelian randomization study - Qu, Yangming; Chen, Lanlan; Guo, Shijie; Liu, Ying; Wu, Hui (Frontiers in Endocrinology, 2023)
Background and objective Uterine leiomyoma is the most common benign tumor in female of reproductive age. However, its causes have never been fully understood. Methods Genetic variables associated with risk factor were obtained from genome-wide association studies. Summary-level statistical data for uterine leiomyoma were obtained from FinnGen and the UK Biobank (UKB) consortium. We used inverse variance weighted, MR-Egger and weighted median methods in univariate analysis. Multivariable MR analysis was used to identify independent risk factors that were significant in the univariate analysis. A fixed-effect model meta-analysis was used to combine the results of FinnGen and UKB. Results In FinnGen, higher genetically predicted age at natural menopause, SBP, DBP and fasting insulin were associated with increased risk of uterine leiomyoma, while higher age at menarche was associated with reduce risk of uterine leiomyoma. Multivariable MR analysis of SBP and DBP showed that higher DBP is an independent risk factor of uterine leiomyoma. In UKB, the results of age at natural menopause, SBP, DBP, and age at menarche were replicated. The result of meta-analysis suggested that uterine leiomyoma could also be affected by PCOS, endometriosis and 2h Glucose. Conclusion Our MR study confirmed that earlier menstrual age, hypertension, obesity, and elevated 2-hour glucose post-challenge were risk factors for uterine leiomyoma, and ruled out the causal relationship between smoking and uterine leiomyoma. In addition, endometriosis was found to increase the risk of uterine leiomyoma, while later age of menopause and PCOS were found to decrease the risk.